Hiccup the seasick Viking - Cowell, Cressida (New York : Orchard Books, 2000)
Unlike his large and brave fellow Vikings, Hiccup is small and afraid of everything until he helps steer his ship to safety during a storm.
First published in Great Britain in 2000 under title: Hiccup, the Viking who was seasick.
13 17
Keywords: Vikings -- Fiction; Fear -- Fiction